(untitled) (MAUSAM, 1988)
The present study is an attempt to develop methods for the long range prediction of monsoon rainfall (June to September) over Dhaka by using correlation technique. Meteorological parameters of the same station, namely, the surface temperature and sea level pressure of February are found to correlate significantly with the rainfall during the monsoon period, for the years 1961-77. Using these parameters prediction equations are developed for the estimation of (a) total rainfall of June to August, (b) rainfall during September and (c) total monsoon rainfall (i.e., June to September). The skills of the derived prediction equations have been examined for a test period of 3 years (1978-80) and are found to be reasonably good in two years.